A Document-Based Study of Strategic Decision-Making in Real Estate Investments by Government-Linked Investment Companies (GLICs) - Aziz, Fatin; Mohd Adnan, Yasmin; Ahmad Baharum, Zarita; Noorame Mohd Foudzy (International Journal of Property Sciences (E-ISSN: 2229-8568), 2025)
This study critically examines institutional investors’ role and strategic approaches in Malaysia’s real estate market, with a particular focus on Government-Linked Investment Companies (GLICs). These entities, encompassing pension funds, mutual funds, special purpose funds, and sovereign wealth funds, function as state investment arms, wielding significant influence over the nation’s economic trajectory. Despite their substantial financial resources and policy-driven mandates, GLICs allocate a disproportionately modest share of their portfolios—typically between 5.3% and 20%—to real estate. This raises critical questions about the underlying constraints, risk perceptions, and structural inefficiencies that may impede a more assertive real estate investment strategy. This research systematically analyses 34 documents, including annual reports, regulatory frameworks, and legislation, and examines the governance and decision-making structures that shape GLIC’s investment strategies. The findings highlight a multi-tiered and strict hierarchy involving Boards, Investment Panels, Shariah Compliance Committees, and Real Estate Departments, employing both top-down and bottom-up approaches. While this structure ensures regulatory compliance and risk mitigation, it may also introduce bureaucratic inertia, limiting responsiveness to market opportunities and emerging asset classes. Furthermore, legislative mandates such as the Employees Provident Fund Act 1991, the Retirement Fund Act 2007, the Tabung Angkatan Tentera Act 1973, and the Tabung Haji Act 1995 impose distinct constraints and investment thresholds that potentially restrict agility in portfolio expansion. A key paradox emerges, despite real estate’s ability to hedge against inflation and provide stable returns, GLICs prefer more liquid asset classes. Their limited allocation to real estate, even with diversification across traditional and non-traditional sector globally, suggests a preference for alternative investments. This trend rises questions about whether regulatory rigidity or cautious investment culture limit the potential of real estate as an asset class. The findings underscore the need for policy recalibrations, governance reforms, and strategic realignments to unlock the full potential of institutional real estate investments. These insights hold significant implications for policymakers, market participants, and researchers at the intersection of finance, governance, and real estate development.